The Crusades in Perspective: The Crusades in Modern Islamic Perspective - Andrea, A. J. (History compass, 2003)
Over the course of the next year, I would like to offer occasional perspectives on the crusades—a series of holy wars waged by the Latin Christian World against primarily the Islamic World of the Middle East and largely during the period 1096-1291.